2007
DOI: 10.1051/ocl.2007.0233
|View full text |Cite
|
Sign up to set email alerts
|

Effect of docosahexaenoic acid in a mouse facial nerve injury model

Abstract: We have previously reported in a model of spinal cord injury that the omega-3 polyunsaturated fatty acid docosahexaenoic acid (DHA) has signifi cant neuroprotective effects after trauma in the central nervous system [1]. In the present study we extend our observations on the neuroprotective and neuroregenerative effects of DHA to a peripheral nerve injury model. Facial nerve transection in mice is a well-established model used in studies on axonal regeneration [2]. We carried out this nerve lesion in mice and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…One aspect concerning the use of -3 PUFAs in neurotrauma that remains to be fully explored is their potential neuroprotective and pro-regenerative effect after PNI. However, -3 PUFAs can enhance neurite outgrowth in cultures of hippocampal and cortical neurons (Calderon and Kim, 2004), as well as in cultures of primary sensory neurons (Robson et al, 2010), and DHA has been shown to increase the number of sprouting fibers after a facial nerve transection (Makwana et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…One aspect concerning the use of -3 PUFAs in neurotrauma that remains to be fully explored is their potential neuroprotective and pro-regenerative effect after PNI. However, -3 PUFAs can enhance neurite outgrowth in cultures of hippocampal and cortical neurons (Calderon and Kim, 2004), as well as in cultures of primary sensory neurons (Robson et al, 2010), and DHA has been shown to increase the number of sprouting fibers after a facial nerve transection (Makwana et al, 2006).…”
Section: Introductionmentioning
confidence: 99%